(untitled) (Journal of Medical & Health Sciences Review, 2025)
Abstract Hypertension is one of the leading causes of cardiovascular diseases, and the condition causes several changes in the heart muscles now referred to as cardiac remodeling. This case-control, cross-sectional study aims to investigate the dynamic changes in hypertensive cardiac morphology and function in patients over time with a follow-up period of 5 years, looking at left ventricular mass, myocardial fibrosis, diastolic and systolic dysfunction, and cardiovascular biomarkers. In the current study, hypertensive patients’ cohort was investigated with echocardiography, cardiac magnetic resonance imaging and strain analysis and measurement of natriuretic peptides and inflammatory biomarkers. The findings presented in the study show an increase in LVMI while there is a transition from compensatory to the detrimental form of cardiac hypertrophy as diagnosed by LGE and higher ECV. This was associated with a progressive decrease in GLS of the left ventricle, an early measure of systolic function even when LVEF remains apparently preserved. This led to a deterioration of diastolic function with increased E/e’ ratio and reduced mitral inflow velocities, increased LAVI and higher risk for the development of atrial fibrillation. High BNPs and elevated hs-TnT index indicated the increase of myocardial stress level and subclinical cardiac damage. thereby, early diagnosis and treatment of hypertensive cardiac remodeling recognized the fact that hypertensive cardiac remodeling plays a critical role in the increasing incidence of cardiovascular events, which include heart failure, arrhythmia, stroke among others. These findings suggest routine, expanding clinical practice that involves myocardial strain measurement, fibrosis imaging, and biomarkers assessment in hypertensive patients. Several interventions for consistently lowering blood pressure, reducing myocardial fibrosis, and clearing inflammation may play the core role in slowing the disease progress. These findings offer vital knowledge of the calendar and ways in which hypertensive heart disease occurs and which other disease develops, and it presents helpful information to use in regard to future research in arresting other unfavorable cardiac consequences among hypertensive patients.